Imitators of severe preeclampsia: on differential diagnosis and multidisciplinary management - A. N. Strizhakov; I. V. Ignatko; E. V. Timokhina (Акушерство, гинекология и репродукция)
Preeclampsia (PE) is not only a disease of pregnant women, but also a disease with lifelong consequences for mother and child. Making an early diagnosis and differential diagnosis of PE is crucial yet challenging, since PE can be mistaken for other internal diseases or surgical conditions. Despite the variety of clinical symptoms of thrombotic microangiopathy that may manifest in a non-typical picture of PE, progressive multiple organ failure develops in all cases. It seems promising to study the role of matrix metalloproteinases and determine the genetic predisposition to early and severe PE. The forecast and prevention attempts must begin from the fertile cycle. A better knowledge of biochemical and genetic markers along with the clinical and instrumental tests will reduce the morbidity and mortality in PE patients.